Sex and Age Differences in Levels of Anomia of Latvian Inhabitants - Ļevina, Jeļena; Mārtinsone, Kristīne; Kamerāde, Daiga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Anomia is one of the important factors, which can influence the psychological well-being of individuals. It is especially valuable to determine those socio-demographic groups which can demonstrate the highest levels of anomia. The purpose of the research was to determine whether there are sex and age differences in levels of anomia of Latvian inhabitants. The secondary data from the third European Quality of Life Survey (EQLS) were used. The sample consisted of Latvian inhabitants (n = 1009), aged from 18 to 92 years (male – 34.9%, female – 65.1%). 3 indices and 3 subscales of anomia (Social Distrust, Social Isolation and Meaninglessness) were constructed (Ļevina, Mārtinsone & Kamerāde, 2015a, 2015b). A multivariate analysis of variance was conducted. It was found that there was a significant difference in multidimensional anomia between Latvian inhabitants of different age groups.